Expiryno: cosmetics expiry date tracker mobile application / Nurfatihah Azmi - Azmi, Nurfatihah (2022)
As cosmetics product has a long shelf life, people tend to be forgetful in remembering the cosmetics expiry date. Therefore, this project developed a mobile application that helps cosmetic users to use voice recognition for cosmetics product details insertion as barcode scanning cannot capture the expiry date of the cosmetics product and to allow the users to be notified of the cosmetic expiry date. The objectives of this project are to identify the user requirement, design, and develop the ExpiryNo: Cosmetic Expiry Date Tracker Mobile Application. In this project, the scope focuses on cosmetic products such as eye makeup, lipstick, and powder and developed via the Android platform. The methodology adopted for the project is the Mobile Application Develop Life Cycle (MADLC) until the testing phase. The features developed are adding cosmetics product details using voice recognition, and push notification. This mobile application is evaluated using the System Usability Scale (SUS) to determine its efficacy and usability. As the average SUS score is 92.5, it is concluded that the majority of users considered the mobile application to be simple to use and that it includes a variety of functionalities that are effectively integrated. For future recommendations, it is proposed to enhance the development of the iOS platform, and enlarge the cosmetics product coverage.